Implementasi Pemberian Cerita Islami dalam Upaya Menanamkan Nilai-Nilai Keagamaan Anak di TK-IT Khairul Imam Kecamatan Medan Johor - Muhammad Riduan Harahap (ABNA : Journal of Islamic Early Childhood Education, 2021)
The development of religion since the beginning of the encouragement and stimulation of trees requires air and fertilizer. Children's interests and aspirations need to be developed in a better and commendable direction through education. After knowing the importance of religious education for children, especially in producing Islamic children, one of the things we feel is that educators can play a role and function in carrying out their teacher duties. Giving Islamic stories and good advice is the right step for children's morals and instilling religious values in children, where at this age children must be stimulated by reason and build stories that educate so that they model the behavior of figures who good and hostile or hate bad behavior. This study describes the moral values that are instilled in children are to form humans who have awareness in carrying out religious orders. The teacher explains what is good and should be imitated and what is not good and should not be imitated in everyday life.